Kisah Ayub sebagi Kritik Pastoral terhadap Stigma kepada ODHA di Gereja Toraja Jemaat Batusura - Capriaty, Jenniver; Maviana, Anggryel; Andri; Junardi (Unit Penerbitan Informasi dan Teknologi Sekolah Tinggi Teologi Gereja Kalimantan Evangelis (STT GKE), 2025)
This research is motivated by the struggle regarding the stigma and discrimination of church members towards PLWHA. PLWHA are stigmatized as sinners because the congregation often identifies HIV/AIDS as a disease caused by sin. The author found this case in the Toraja Church, Batusura Congregation. To minimize cases of discrimination in the congregation's perspective towards PLWHA, the author analyzed the pastoral approach model found in the story of Job. Job's suffering is a critique of retributive theology which always generalizes disease as a result of sin. Job's friends visited Job and helped him understand his suffering with a deductive pastoral approach and retributive theology as the basis of thinking. However, God showed Job's friends the error and claimed that Job's suffering was under the authority of His wisdom and creativity. The author found that Job's story emphasizes a correlational pastoral approach. This approach rejects discrimination and generalization towards PLWHA because not all diseases are the result of sin, including PLWHA. The stigma of a sinner will not restore PLWHA but instead discriminate against them. A correlational approach can also help congregations encounter other causes of HIV/AIDS that are not sinful acts.